2022
DOI: 10.1097/scs.0000000000008471
|View full text |Cite
|
Sign up to set email alerts
|

Reflecting on Plastic Surgery Training During Early COVID-19 Pandemic: Resident Exposure and Telemedicine

Abstract: Purpose: Coronavirus disease 2019 (COVID-19) pandemic has been an unprecedented public health crisis. As hospitals took measures to increase their capacity to manage COVID-19 patients, plastic surgeons have also had to modify their routine to continue serving their vital role within the hospital environment. In an effort to reduce exposure to COVID-19 and conserve hospital resources, many plastic surgery programs drastically modified call schedules, restructured inpatient teams, triaged operative cases, and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Moreover, digital platforms increasingly play a major role in clinical academic research, surgical training and are regularly used for communication and networking between healthcare professionals [ 15 , 16 ]. While on-site surgical training was temporarily critically disrupted by redeployment of the trainees and pandemic restrictions, virtual training was successfully implemented [ 17–19 ]. To guarantee continuity of health care services, especially during the COVID-19 pandemic, virtual clinics, multidisciplinary team meetings and augmented reality in live surgery in virtual cooperation with surgeons on a different continent became daily business [ 11 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, digital platforms increasingly play a major role in clinical academic research, surgical training and are regularly used for communication and networking between healthcare professionals [ 15 , 16 ]. While on-site surgical training was temporarily critically disrupted by redeployment of the trainees and pandemic restrictions, virtual training was successfully implemented [ 17–19 ]. To guarantee continuity of health care services, especially during the COVID-19 pandemic, virtual clinics, multidisciplinary team meetings and augmented reality in live surgery in virtual cooperation with surgeons on a different continent became daily business [ 11 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been published that examine how the COVID-19 pandemic has impacted plastic surgery resident training 5–7,10 . Jabori et al 6 administered a survey to plastic surgery trainees in the United States and found a perceived decrease in operative experience as well as an increase in virtual learning via webinars and online modules.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been published that examine how the COVID-19 pandemic has impacted plastic surgery resident training. [5][6][7]10 Jabori et al 6 administered a survey to plastic surgery trainees in the United States and found a perceived decrease in operative experience as well as an increase in virtual learning via webinars and online modules. Crowe et al 10 deployed a survey that revealed 58.1% of plastic surgery trainees felt that the COVID-19 pandemic had a negative impact on their education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations